In black and white a novel - Tanizaki, Jun'ichirō 1886-1965 (Weatherhead books on Asia, 2017)
"Black and White is a full translation of Tanizaki Jun'ichirō's 1928 novel, Kokubyaku, with an introduction that identifies the special conditions that might have made it a "lost" novel. This novel offers a window into Tanizaki's life and work at a critical transition point in his career. The introduction focuses on the moment Tanizaki astounded the literary world in 1928 by writing three novels in the same year, after several years of relative silence following the 1923 Great Kantō Earthquake. Two of the three (Some Prefer Nettles and Quicksand) immediately became famous; this third disappeared from view. The novel tells the story of a writer who in essence kills another writer with his writing. In it, an obsessive paranoid fantasy turns out to invade "real life," and it ends with a man confessing to a murder he did not commit. Over the course of the story, he (the character? the author?) invents a character he calls the "Shadow Man," who is out to entrap the writer (the protagonist? the author?) and destroy him. The tone of the story is comic rather than tragic, sardonic rather than dramatic. There is a peculiar ambiguity between author and character that distinguishes the story from the usual "I-novel" genre of the day; the novel is autobiographical in an unusual way, although Tanizaki was never considered an autobiographical writer. The central questions the introduction addresses are: What is autobiographical in the novel; who was killed and why; and how did that elimination help make Tanizaki a great writer?"--